A Narrative Account of Health Promotion in Schools: Encouraging Hand Washing - Oberto, María Georgina (2020)
Encouraging healthy habits in schools through appropriate teaching strategies and resources  promotes good health. The objectives of this study are to instill correct hand washing techniques as a method of preventing foodborne illnesses and other diarrheal and respiratory diseases, strengthen daily hygiene practices at two schools in Cordoba, Argentina during a two-year period of 2016-2018, specifically  among pre-school and primary school levels, and, finally, develop educational materials on hand washing. Health promotion activities were conducted by five instructors and ten students from the National University of Córdoba. Each year, an assessment of the situation was made to introduce the teaching teams and agree on how the information would be presented while taking the school curriculum into account. Educational workshops were carried out with practical work in school restrooms to teach proper handwashing. During the 2016 and 2018 period, 504 students and 20 teachers from both schools attended the workshops. The outputs resulted in a children's book, dissemination posters and 32 examples of original artwork by children to be used as educational material which was exhibited at an event called, Night of the Museums  in 2018.  The workshops and outputs were readily accepted and considered appropriate by the school teachers. As a result, girls displayed better assimilation of hand washing after using the toilet more than boys. Yet, the number of students that acquired the habit was lower than expected. It was concluded, however, that schools are favorable environments to encourage and promote  healthy behaviors, but that more work is needed to continue to strengthen this practice.